AKSESIBILITAS HALTE TRANS JOGJA TERHADAP POTENSI KAWASAN - , ANGLING RANDHIKO PUTRO, Ir. Ikaputra, M.Eng, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Urbanization cause the increase transportation needs in urban space because human movement patterns keep increasing and make streets fuller and traffic jams unavoidable. Mass transportation is a way to provide mobility service in all areas and activity centers. For people to maximize using mass transportations for their mobility, the ease in accessing transportation system, in this case Trans Jogja shelters based on Transit Oriented Development, should also be planned well. Area accessibility to Trans Jogja shelters should be increased or the public should be given the options of public and private transports or walking to reach and leave the shelters. This research describes accessibility system of Trans Jogja shelters users by optimizing transit points and providing accessibility systems between modes and pedestrian way to potential destinations of the areas to increase comfort and ease of the users of Bus Rapid Transit Trans Jogja. The recommendation is to focus on ease and comfort for streetwalkers, road signs leading to Trans Jogja shelters, accessibility defined as pedestrian ways with proper shades, no conflict and little crossing with motor vehicles, parking spaces for public and private transportations for the users of shelters who change transportation modes.